Modelling of MEMS vibratory gyroscopes utilizing phase detection - Dreyer, Antonie Christoffel (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2008.